Genetic Diversity Analysis of Sapota (Manilkara Zapota) Germplasm by Rapd Marker (Bangladesh Journal of Agricultural Research, 2022)
The experiment was carried out at the Department of Horticulture, Patuakhali Science and Technology University (PSTU), Bangladesh, during the period from October 2018 to April 2019. The genetic diversity of eight sapota germplasm viz. Gp-1, Gp-2, Gp-4, Gp-6, Gp-7, Gp-9, Gp-15 and Gp-17available at the Germplasm Center of PSTU using PCR based Random Amplified Polymorphic DNA (RAPD) marker were studied.By the PCR, the RAPD primers generated various bands ranging from 3 to 10 and yielded a total of 45 bands of which 42.12% were polymorphic.Comparatively higher genetic distance (0.28) was found between Gp-1 and Gp-9. The inter-population similarity index value was the highest (99%) between Gp-2 and Gp-9, Gp-4 and Gp-15.Among the germplasm, Gp-1 and Gp-17werethe most polymorphic with other sapotagermplasm. Interestingly, the leaf morphological features (length and width) were also found the highest in Gp-1 and Gp-17.Bangladesh J. Agril. Res. 45(2): 145-155, June 2020